Total quality management and business performance in the security service industry: A pilot study - Abdul Wahab, Mohd Hafeez Al-Amin; Che Cob, Che Mohd Syaharuddin; Setapa, Mariam; Mohamad, Mohamad Sukram; Azmi, Muhammad Izhan; Amir, Muhammad Adammi (Journal of Islamic, Social, Economics and Development, 2026)
This study examines the key dimensions of Total Quality Management (TQM) practices and business performance in the security services industry. The survey questionnaires were designed and distributed to 50 respondents within a Malaysian security service organisation. The pilot study sample consists of 30 respondents from 50 questionnaires, with an average response rate of 60%. Reliability and validity tests were conducted, and the data were analysed using the Statistical Package for the Social Sciences (SPSS). The results indicate that four main TQM dimensions, namely leadership, benchmarking, continuous improvement, and human resource management, demonstrate satisfactory reliability and measurement adequacy. Furthermore, leadership emerged as the most prominent dimension supporting the implementation of TQM practices within the organisation. This research concludes that the identified TQM dimensions provide a reliable foundation for assessing business performance in the security services industry. Thus, further studies are recommended to investigate and validate the structural relationships between TQM practices and business performance in the Malaysian security services industry.